Psychological and utility-based quality of life impact of screening test results for anal precancerous lesions in gay and bisexual men: baseline findings from the Study of the Prevention of Anal Cancer. (1st August 2019) - Cvejic, Erin; Poynten, Isobel Mary; Kelly, Patrick J; Jin, Fengyi; Howard, Kirsten; Grulich, Andrew E; Templeton, David J; Hillman, Richard J; Law, Carmella; Roberts, Jennifer M; McCaffery, Kirsten
Abstract : Objective: Gay, bisexual and other men who have sex with men (GBMSM), particularly HIV-positive GBMSM, are at increased anal cancer risk compared with the general population. This study examined the psychological and quality of life (QoL) impact of receiving abnormal anal cancer screening results during the baseline visit of the Study of the Prevention of Anal Cancer (SPANC). Methods: SPANC was a prospective cohort study of the natural history of anal human papillomavirus (HPV) and associated abnormalities in GBM aged 35 years and over. Participants completed questionnaires including aspects of health-related QoL (HR-QoL) and psychosocial functioning at baseline. Participants underwent procedures including an anal swab for cytology, and high-resolution anoscopy with biopsy of any possibly HPV-related abnormality. Questionnaires were readministered 2 weeks and 3 months after participants were given cytology and histology results. Perceived test result served as the study factor. Results: Participants with perceived abnormal results (n=232) reported poorer HR-QoL (mean difference=1.8; p=0.004) and lower utility-based QoL (mean difference=0.02; p=0.018) 2 weeks after screening than individuals with perceived normal results (n=268). These differences did not persist at 3-month follow-up. A greater proportion of participants who perceived their results as abnormal reported feeling worse than usual about their anal health and anal cancer fear (p's<0.001), experienced more intrusive thoughts about their results (p's≤0.006) and felt more likely to develop cancer than other gay men their age (p's≤0.025) at both time points than those with perceived normal results. Conclusions: Providing abnormal results may cause psychological distress and impact HR-QoL, with sustained intrusive thoughts, increased cancer worry and perceived cancer risk. The potential for psychological harm needs to be considered when implementing anal cancer screening programmes.